16S rRNA Gene Copy Number Normalization Does Not Provide More Reliable Conclusions in Metataxonomic Surveys - Starke, Robert; Pylro, Victor Satler; Morais, Daniel Kumazawa (Microbial ecology, 2021)
Sequencing 16S rRNA gene amplicons is the gold standard to uncover the composition of prokaryotic communities. The presence of multiple copies of this gene makes the community abundance data distorted and gene copy normalization (GCN) necessary for correction. Even though GCN of 16S data provided a picture closer to the metagenome before, it should also be compared with communities of known composition due to the fact that library preparation is prone to methodological biases. Here, we process 16S rRNA gene amplicon data from eleven simple mock communities with DADA2 and estimate the impact of GCN. In all cases, the mock community composition derived from the 16S sequencing differs from those expected, and GCN fails to improve the classification for most of the analysed communities. Our approach provides empirical evidence that GCN does not improve the 16S target sequencing analyses in real scenarios. We therefore question the use of GCN for metataxonomic surveys until a more comprehensive catalogue of copy numbers becomes available.
Keywords: Gene; Metagenomics; metagenomika; 16S rRNA; mikrobiota; Gene Library; Microbiota; RNA, Ribosomal, 16S; Gene Dosage; genová dávka; Metagenome; Metataxonomic surveys; genová knihovna; metagenom; RNA ribozomální 16S